LITERATURE REVIEW: ANALISIS HUBUNGAN KEPATUHAN PROTOKOL KESEHATAN DENGAN RISIKO PENULARAN COVID-19 DI MASYARAKAT - Supatmi, Supatmi (Journal Healthcare Education, 2023)
The Analysis of the Relationship between Compliance with Health Protocols and the Risk of Transmission of COVID-19 in the Community delves into the intricate dynamics surrounding public adherence to health protocols and its impact on the transmission risk of COVID-19. The findings emphasize the pivotal role of effective policies, community preparedness programs, and heightened public awareness in mitigating the transmission risk. The comprehensive review incorporates various perspectives, such as gender, risk perception, government measures, and social support, to provide a holistic understanding of the multifaceted relationship between compliance with health protocols and COVID-19 transmission risk in communities. The methodology involves a systematic literature review, applying inclusion and exclusion criteria to select relevant and high-quality articles. The synthesis and critical evaluation of empirical findings aim to present a comprehensive understanding of the complex dynamics between health protocol compliance and COVID-19 transmission risk at the community level. The results underscore the importance of tailored interventions, effective risk communication, and resilience-building activities to enhance compliance and reduce transmission rates. Overall, the study contributes valuable insights for policymakers, healthcare professionals, and the general public in navigating the ongoing challenges of the COVID-19 pandemic.